Lectures in multisensor data fusion and target tracking - Hall, David L. (David Lee), 1946-; Hall, David L. (David Lee), 1946- (Boston : Artech House, 2001)
Serves as a self-contained course on multisensor data fusion and target tracking. Based on, and be used with Mathematical Techniques in Multisensor Data Fusion by David L. Hall. Covers data fusion and target tracking fundamentals, data fusion systems, sensor technology and single sensor processing, sensor management and control and automated reasoning systems for situation and threat assessment, the role of man/human-in-the-loop, and the current state of the art
System requirements : Windows or Macintosh ; Adobe Acrobat Reader (included on disc) ; CD-ROM drive
Keywords: Signal processing; Multisensor data fusion -- Mathematical models